2020
DOI: 10.3389/fmicb.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Quantitative Trait Loci Associated With Resistance to Aflatoxin Accumulation in Maize Inbred Mp719

Abstract: Aflatoxins are carcinogenic and toxic compounds produced principally by fungal species Aspergillus flavus (Link: Fries) and A. parasiticus (Speare), which are common contaminants of food and feed. Aflatoxins can be found at dangerously high levels and can readily contaminate pre-harvest maize (Zea mays L.) grain. Sources of resistance to aflatoxin accumulation in maize have been identified, however, the highly quantitative nature and complex inheritance of this trait have limited the introgression of aflatoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…As a similar result was reported recently [ 25 ]; we concluded that there is no reason to test their resistance separately. The only reason for using F. culmorum is its lower temperature requirement; therefore, in cooler summers, higher infection rates can be achieved than working with only F. graminearum [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a similar result was reported recently [ 25 ]; we concluded that there is no reason to test their resistance separately. The only reason for using F. culmorum is its lower temperature requirement; therefore, in cooler summers, higher infection rates can be achieved than working with only F. graminearum [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…of the QTL (Edwards, 1992). To find markers linked to preharvest aflatoxin accumulation resistance, several QTL mapping and genome-wide association studies have been conducted (e.g., Brooks et al, 2005;Dhakal et al, 2016;Farfan et al, 2015;Warburton et al, 2009Warburton et al, , 2011Warburton et al, , 2015Womack et al, 2020).…”
Section: Core Ideasmentioning
confidence: 99%
“…Markers for the quantitative trait loci (QTL) correlated with resistance could be used for marker‐assisted selection (MAS) and “targeted introgression” of the QTL (Edwards, 1992). To find markers linked to preharvest aflatoxin accumulation resistance, several QTL mapping and genome‐wide association studies have been conducted (e.g., Brooks et al., 2005; Dhakal et al., 2016; Farfan et al., 2015; Warburton et al., 2009, 2011, 2015; Womack et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin contamination, which is caused by a pathogen, namely, Aspergillus flavus , is a huge threat to the peanut industry and other important crops such as corn, rice, and wheat (Mahato et al, 2019 ; Womack et al, 2020 ). Contaminated agricultural products could endanger the health of human beings and animals (Pittet, 1998 ; Desjardins, 2003 ; Kew, 2013 ).…”
Section: Introductionmentioning
confidence: 99%